Kepakaran dan tanggungjawab jawatankuasa Syariah dalam menguruskan risiko ketidakpatuhan Syariah: tinjauan awal terhadap industri takaful di Malaysia / Mohd Faiz Mohamed Yusof, Nurhanani Romli and Joni Tamkin Borhan - Mohamed Yusof, Mohd Faiz; Romli, Nurhanani; Borhan, Joni Tamkin (Universiti Teknologi MARA, Pulau Pinang, 2014)
This study identifies the potentials of Shariah non-compliance risk exposures of takaful industry in Malaysia based on previous studies.Besides, this study also examines the areas of expertise of the Shariah Committee of the Takaful Operator (TO) in Malaysia with a total of 62 members. Bank Negara Malaysia (2003) requires the expertise and experience in fiqh and usul fiqh, or Fiqh Muamalat among the Shariah Committee in TO. The expertise and experience in the field of fiqh and usul fiqh or fiqh muamalat are extremely important in managing Shariah non-compliance risk.